Pengetahuan pengguna tentang kematangan karir ditinjau dari kualitas informasi pada Instagram @glintsid - Fina Nurul Zakiyyah; Nuning Kurniasih (Jurnal Informatio, 2023)
Glints Indonesia is one of the media that is commonly used as an ecosystem for career maturity, career development, and online-based job recruitment. Not only active through the website, but Glints Indonesia is also active through the Instagram platform with the username @glintsid. The information contained in @glintsid's post suggests new knowledge to its users. This study aims to determine user knowledge about career maturity in terms of the quality of Instagram @glintsid on career tips content. The research method used in this research is qualitative.descriptive Data collection techniques used is observation and interviews with 5 (five) respondents who are final year students of Universitas Padjadjaran who are also Instagram followers @glintsid. The data analysis method used in this research includes data reduction, data presentation, and conclusion. The results of this study indicate that @glintsid's Instagram posts have fairly information quality with accurate, relevant, timely, and completeness indicator. Respondents found that the information content of @glintsid's posts is easy to understand, relevant to needs, timeliness, and clear enough to avoid ambiguity in seeking career tips. In terms of user knowledge indicators, respondents considered that the presence of career tips content on Instagram @glintsid had increased their knowledge through fulfilling indicators such as career planning, career exploration, knowledge about decision making, a world of work information, knowledge of preferred occupation group, and knowledge about the realization of career decisions. The study results show that the quality of information on Instagram @glintsid is quite good and can add new knowledge to respondents.